BUILDING THE TRANSFORMATIVE ISLAMIC CIVILIZATION REASERCH ON GAIT OF K.H. M.A. SAHAL MAHFUDH - Ma'mur, Jamal (LPPM IAIN Kudus, 2017)
Historical evidence shows that K.H. M.A. Sahal Mahfudh is building the transformative Islamic civilization towards g a prosperous, fair, and progressive Muslim community buildings. Kiai Sahal Mahfudh encourages Muslims to be the best people able to provide profusely expediency to others. According to Kiai Sahal Mahfudh, the best people are productive people, the man who is sensitive to the needs of the environment, controlling information, having organizational competence and high creativity, so that they can create jobs and grow the economy comprehensive insight. For these ideals, the aspect of education, health, and the economy must be developed maximally. These three fields are interrelated and inseparable. Transformative Islamic civilization championed by Kiai Sahal Mahfudh is relevant to maqasidus sharia theory, that is the Islamic law which purposes to keep religion, keep the soul, keep the property, keep the mind and keep the offspring. Kiai Sahal Mahfudh struggle in improving the quality of education in boarding school and university Maslakul Huda, Islamic Mathaliul Falah Kajen in order to keep religion and reason. Economic empowerment in BPPM and BPR Artha Huda Abadi in order to keep the property. While the struggle of Kiai Sahal Mahfudh in establishing Islamic Hospital Pati in order to preserve life and heredity. This study is a qualitative research with the primary sources of Kiai Sahal Mahfudh works. The result of this study is analyzed by the theory of maqasid asy-syari‘ah.